Operations Management. - B, Mahadevan (2010)
Operations Management: Theory and Practice aims to introduce the key concepts of production and operations management to students and to help them develop a sound conceptual understanding of the subject by adopting a practical approach to address various topics relevant to operations management. While preserving the much-appreciated features of the first edition-the Ideas at Work boxes, the solved examples, and the rich examples of operations management practices in India-the second edition has been revised to increase the coverage of the service sector, include more topics, reorganize chapter content, and provide more learning tools.
IDEAS AT WORK 9.1: MOTHER DAIRY: A CASE FOR SUPPLY CHAIN MANAGEMENT?.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books